Comparison in Levels of Interleukin 6, Ferritine and Neutrophil-Lymphocyte Ratio in COVID-19 Patiens Treated in ICU and Non-ICU - Nanda Oktavia; Efrida Efrida; Zelly Dia Rofinda (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Inflammation is caused by infectious diseases, including COVID-19. Severe inflammatory responses contribute to weak adaptive immune response, there by resulting in immune response imbalance. Circulating biomarkers can represent inflammation and immune status are potential predictors for the prognosis of COVID-19 patients. Ferritin and interleukin-6 can serve as significant biomarkers in the detection of cytokine storm, systemic inflammation, and the prognosis of COVID-19. Neutrophil-lymphocyte ratio is an independent prognostic biomarker for COVID-19 patients. The aim of this study to determine differences levels of IL-6, ferritin, and NLR in COVID-19 patients treated ICU and non-ICU. This study was comparative cross-sectional design of 62 COVID-19 patients. Research was conducted at the Central Laboratory and Medical Record of Dr. M. Djamil Padang hospital (May-September 2021). Interleukin-6 levels determined the ECLIA methods, ferritin with the ELFA methods, and NLR with calculation methods. Bivariate data were analyzed with Mann-Whitney test. The characteristics of COVID-19 patients treated in ICU: 64.5% male, average age was 53.52(10.71) years, 48.4% death, and non ICU: female 71.0%, average 42.32 (12.22) years, and recovered 100%. The most common comorbid is hypertension. There were significant differences levels of IL-6, ferritin, and NLR in ICU and non-ICU patients with COVID-19 (p<0.001).